Skills of Smash Backhand on Table Tennis of 3 Dimensional Based on Multimedia - Dlis, Firmansyah; Hanif, Ahmad Sofyan (International Journal of Psychosocial Rehabilitation, 2020)
This study aims to determine the effect of training methods and functional movement on strokes technical skills on the backhand smash in the table tennis game. This research was conducted at table tennis athletes in the city of Makassar. The method used is an experiment using a 2x3 factorial design. The sample consisted of 60 athletes, divided into 6 groups, each consisting of 10 athletes. The data analysis technique used is the analysis of two-way variance (ANOVA) and continued with the t-Dunnet test at the level of significance α = 0.05. The results showed that: the distributed practice method has a higher effect than the massed practice method on backhand smash skills, the massed practice method is more effect than the mixed practice method for smash backhand skills, methods distributed practice has more effect than the mixed practice method on smash backhand skills, there is interaction between the massed practice method, distributed practice method, mixed practice method, and functional movement on backhand smash skills, massed practice method is higher than mixed method practice on smash backhand skills in high functional movement groups, distributed practice methods are higher than mixed practice methods of smash backhand skills in high functional movement groups, distributed practice methods are higher than massed practice methods of smash backhand skills in low functional movement groups, Mixed practice methods are higher than the massed practice method of low functional movement smash backhand skills. Multimedia technology comes using Kinovea, as a software that has been created specifically for sports professionals and their coaches.